Design of cathodic protection for the Kadikoy pretreatment plant sea outfall, Istanbul, Turkey - Akkoyunlu, A; Cizmecioglu, Z; Ertürk, F; Bayhan, H; Yetilmezsoy, K (NATL ASSN CORROSION ENG, 2005)
Sacrificial anode cathodic protection (CP) was designed for the outfall line from a pretreatment plant. The pipeline system consists of a concrete-coated, epoxy-lined steel pipe carrying plant wastewater effluent. Required current densities (CDs) for the pipes and resistivities for seawater, soil, and the waste water running in the pipe were determined. The experimental CD in the seawater was 28.29 mA/m(2) and the CD in the waste water was 3.96 mA/m(2). The design of CP has been developed by considering the corrosive factors of the electrolytes. Aluminum indium sacrificial anodes were chosen for the seawater pipe exterior. Magnesium anodes were selected for the pipe interior and the exterior of the portion of the pipe buried on land.
Keywords: CONCRETE; SEAWATER; Materials Science